STEM research trends in indonesia: A systematic literature review - Dita Ardwiyanti; Zuhdan Kun Prasetyo; Insih Wilujeng (Journal of Science Education Research, 2021)
STEM can contribute to the achievement of Sustainable Development Goals (SDGs) through the development of 21st-century skills. It triggered a massive innovation in science education research on the STEM theme including Indonesia. This content analysis study aimed to systematically analyze STEM research trends in Indonesia based on articles published in national and international journals. Based on the inclusion criteria established, 50 articles were collected to be analyzed using the Paper Classification Form (PCF) instrument. The findings of the analysis indicated a dominance on the topic of learning strategies (54%) with the experimental method (46%). The most common integration pattern found is STEM-PjBL (34.48%). Learning outcomes (23.91%) and scientific literacy (21.74%) were the dependent variables that were dominantly associated with STEM learning. Thus, there needs to be a variety of STEM research on other potential issues to help the government accelerate the achievement of SDGs.